THE USE OF PICTURE BOOKS IN TEACHING LITERACY TO THE NINTH GRADE STUDENTS AT SMP UNISMUH MAKASSAR - Samirah, Bau Sarah; Qalbi, Nur; Mahmudah, Dzur Rif'ah (English Language Teaching Methodology, 2024)
The objective of the research is to know whether or not there is a significant difference for the ninth grade students at SMP Unismuh makassar before and after taught by picture books in teaching literacy. The researcher used a pre-experimental method with one group pre-test and post-test, and data collection based the tests. The sample of this research was IX A class which consist thirty three students. The sample was taken by using purposive sampling technique. Based on the finding of the reserach, the researcher was found there was significant difference in teaching literacy focused on reading comprehension to the ninth grade srudents at SMP Unismuh Masassar. It was proved by the mean score of the post-test 83.2% was higher than the mean score of pre-test 61.3%. it could be proven by the value of the t-test ( 18.456) was higher than the t-table value (1.694)